2021
DOI: 10.1016/j.heliyon.2021.e07822
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and biochemical responses of Macrotyloma uniflorum (Lam.) Verdc. to allelopathic effects of Mikania micrantha Kunth extracts

Abstract: Allelopathic impacts of Mikania micrantha Kunth were investigated on the rate of seed germination, growth, biomass, photosynthetic pigments, total soluble protein, phenolics and proline content of Macrotylama uniflorum (Lam.) Verdc. The extracts inhibited germination, growth, biomass, chlorophyll, carotenoid and protein contents. The protein content of M. uniflorum decreased to 8.48 mg/g at 200 mg/ml. Similarly shoot length, root length also decreased up to 5.11 cm, 0.85 cm respectively and water content incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Higher rates of photosynthesis connected to higher chlorophyll content can lead to increased growth rates, biomass accumulation and overall production ( Shen et al, 2019 ). The chlorophyll-a, chlorophyll-b and carotenoid content of Macrotyloma uniflorum showed decreasing effects upon exposure to Mikania micrantha extracts ( Jali et al, 2021 ). In the present study, we found that both the chlorophyll-a and chlorophyll-b content of L. multiflorum were greatly reduced with increasing concentration of PA, LA, and EP.…”
Section: Discussionmentioning
confidence: 99%
“…Higher rates of photosynthesis connected to higher chlorophyll content can lead to increased growth rates, biomass accumulation and overall production ( Shen et al, 2019 ). The chlorophyll-a, chlorophyll-b and carotenoid content of Macrotyloma uniflorum showed decreasing effects upon exposure to Mikania micrantha extracts ( Jali et al, 2021 ). In the present study, we found that both the chlorophyll-a and chlorophyll-b content of L. multiflorum were greatly reduced with increasing concentration of PA, LA, and EP.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in their amounts after phytotoxic treatments has been recorded by previous investigations. Jali et al (2021), reported that chlorophyll a, b and total contents were negatively affected upon the application of phytotoxic extracts on the species Macrotyloma uniflorum. Regarding carotenoids contents, many studies have reported that the accumulation of these pigments decreases significantly in treated plants (Ghimire et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that phenolic allelochemicals were able to decrease the protein content through the inhibition of protein biosynthesis, or proteolysis (Singh et al 2008), or oxidative adjustment (Fazeli et al 2007). The reduction in protein content can be due to inhibition of the synthesis process, disruption in the translation pathway or activation of other protective mechanisms against stress caused by allelochemical compounds (Knox 2010;Jali et al 2021). In the intercropping of wheat and redroot pigweed, an increase in the protein content was observed at different intercropping ratios in wheat and redroot pigweed roots.…”
Section: Discussionmentioning
confidence: 99%